2010
DOI: 10.1063/1.3324700
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational resonance in neuron populations

Abstract: In this paper different topologies of populations of FitzHugh-Nagumo neurons have been introduce to investigate the effect of high-frequency driving on the response of neuron populations to a subthreshold low-frequency signal. We show that optimal amplitude of high-frequency driving enhances the response of neuron populations to a subthreshold low-frequency input and the optimal amplitude dependences on the connection among the neurons. By analyzing several kinds of topology (i.e., random and small world) diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(53 citation statements)
references
References 18 publications
3
49
0
1
Order By: Relevance
“…The occurrence of the VR phenomenon has been widely studied and reported by many researchers numerically [1][2][3] and experimentally [4][5][6][7][8]. Much studies have been carried out in a large class of dynamical systems such as monostable system [9], excitable system [10], bistable systems [1,11,12], time-delayed system [13] and also in a few lowdimensional maps [14] due to its importance in exhibiting the response of the system in an interesting way.…”
Section: Introductionmentioning
confidence: 98%
“…The occurrence of the VR phenomenon has been widely studied and reported by many researchers numerically [1][2][3] and experimentally [4][5][6][7][8]. Much studies have been carried out in a large class of dynamical systems such as monostable system [9], excitable system [10], bistable systems [1,11,12], time-delayed system [13] and also in a few lowdimensional maps [14] due to its importance in exhibiting the response of the system in an interesting way.…”
Section: Introductionmentioning
confidence: 98%
“…The occurrence of vibrational resonance has been analyzed in systems with monostable [11], bistable [3][4][5], spatially periodic states [12], excitable systems [13,14], coupled oscillators [15] and small world networks [14,16,17]. Experimental evidence of vibrational resonance in vertical cavity laser system [18][19][20] and in an electronic circuit [21] has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we set the threshold = 0 in the calculation of . If < , is replaced by a fixed value = −1; otherwise, remains the same [13,18]. Larger indicates better synchronization between input LF signal and the output of the system and thus also suggests more information transported through a particular forcing frequency [13].…”
Section: Complexitymentioning
confidence: 99%
“…For example, Ullner et al studied the influence of additive noise and the interplay between SR and VR and found that the response of an excitable system to a low-frequency signal can be enhanced by high-frequency driving [12]. Deng et al investigated the effect of HF force on the detection of a subthreshold low-frequency signal in neuron populations with different topology structures and hybrid synapses [18,19]. Yao and Zhan found that signal detection and transmission can be effectively enhanced by VR in oneway coupled bistable systems [20] or a spatially periodic force in the reaction-diffusion system [21].…”
Section: Introductionmentioning
confidence: 99%